Assessment of the COVID-19 vaccine market landscape in 2021 relative to challenges in low- and middle-income countries - D. August Oddleifson; Jehanzeb Kayani; Rhea Shrivastava; Jenny Tan; Maike Winters; Howard Forman; Saad B. Omer (Taylor & Francis Group, 2022)
To evaluate the early vaccine landscape relative to challenges faced by low- and middle-income countries (LMIC), we conducted a cross-sectional study of all COVID-19 vaccines in clinical trials in 2021 (n = 123) using a structured 13-point analytic framework. Supply sustainability was defined as a composite metric of four manufacturing and regulation variables. Vaccine desirability was defined as a composite metric of nine development and distribution variables. Ten vaccines in phases 2/3, 3, or 4 and five vaccines in phases 1 and 1/2 had a sustainability score equal to or above 0.5. Ten vaccines in phases 2/3, 3, or 4 and seven vaccines in phases 1 and 1/2 had a desirability score equal to or above 0.5. No vaccines in Phases 2/3, 3, or 4 met more than one distribution criterion. Structured assessment COVID-19 vaccine candidates in clinical trials in 2021 revealed numerous challenges to adequate access in LMICs. Key policy recommendations included increasing technology transfer to LMICs, developing international legal mechanisms to prevent export bans, and increasing investment in vaccine candidates with more favorable distribution profiles.